Cover Feature: Solid‐State Hydrogen‐Bond Alterations in a [Co2Fe2] Complex with Bifunctional Hydrogen‐Bonding Donors (Chem. Eur. J. 31/2019). Issue 31 (3rd May 2019) - Nihei, Masayuki; Yanai, Yuta; Natke, Dominik; Takayama, Ryo; Kato, Marina; Sekine, Yoshihiro; Renz, Franz; Oshio, Hiroki
Abstract : Molecules exhibiting solid‐state alterations of p K a by external stimuli are expected to be a useful switching unit in multifunctional molecular solids. It was shown that solid‐state alterations of hydrogen‐bonding interactions induced by solvent release and thermal intramolecular electron transfers in a hydrogen‐bonding donor–acceptor system composed of external stimuli‐responsive [Co2 Fe2 ] 2+ cations. More information can be found in the Communication by M. Nihei, H. Oshio, et al. onpage 7449 .